2016
DOI: 10.18383/j.tom.2016.00187
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Effect of Spectroscopic MRI as a Metric for Radiation Therapy Planning in Patients with Glioblastoma

Abstract: Due to glioblastoma’s infiltrative nature, an optimal radiation therapy (RT) plan requires targeting infiltration not identified by anatomical magnetic resonance imaging (MRI). Here, high-resolution, whole-brain spectroscopic MRI (sMRI) is used to describe tumor infiltration alongside anatomical MRI and simulate the degree to which it modifies RT target planning. In 11 patients with glioblastoma, data from preRT sMRI scans were processed to give high-resolution, whole-brain metabolite maps normalized by contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…This group reported abnormal pretreatment sMRI volumes predicted for the sites of eventual glioblastoma recurrence, and the retrospective integration of these abnormal volumes (defined at Cho/NAA thresholds of 1.5, 1.75 and 2.0 greater than contralateral white matter) into the original treatment plans would have improved coverage of the recurrent disease (92.4%, 90.5%, and 88.6%, respectively) compared to the original treatment (82.5%) while maintaining dosimetric constraints. [177] An example is shown demonstrating regions of disease recurrence were previously identified by pre-treatment Cho/NAA maps despite not being apparent on the initial T1 post-contrast and/or FLAIR sequences (Fig. 3B).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 94%
“…This group reported abnormal pretreatment sMRI volumes predicted for the sites of eventual glioblastoma recurrence, and the retrospective integration of these abnormal volumes (defined at Cho/NAA thresholds of 1.5, 1.75 and 2.0 greater than contralateral white matter) into the original treatment plans would have improved coverage of the recurrent disease (92.4%, 90.5%, and 88.6%, respectively) compared to the original treatment (82.5%) while maintaining dosimetric constraints. [177] An example is shown demonstrating regions of disease recurrence were previously identified by pre-treatment Cho/NAA maps despite not being apparent on the initial T1 post-contrast and/or FLAIR sequences (Fig. 3B).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 94%
“… 57 The metabolic information from MRSI can be added to the information from conventional anatomical MRI, leading to a higher coverage of recurrent contrast-enhancing tumor and a more precise estimation of disease extent. 58 Cordova et al showed that MRSI-based target volume identified significantly different regions of microscopic tumor infiltration than conventional clinical target volumes and exhibited better coverage of contrast-enhancing tumor at recurrence in two out of seven patients. 11 In a multisite pilot study which aimed at establishing feasibility and safety of dose-escalated RT based on metabolic abnormalities in patients with GBM, Gurbani et al developed the Brain Imaging Collaboration Suite which is a cloud platform that combines whole-brain MRSI and MRI data and allows members from different institutions to define RT targets.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“… 58 Cordova et al showed that MRSI-based target volume identified significantly different regions of microscopic tumor infiltration than conventional clinical target volumes and exhibited better coverage of contrast-enhancing tumor at recurrence in two out of seven patients. 11 In a multisite pilot study which aimed at establishing feasibility and safety of dose-escalated RT based on metabolic abnormalities in patients with GBM, Gurbani et al developed the Brain Imaging Collaboration Suite which is a cloud platform that combines whole-brain MRSI and MRI data and allows members from different institutions to define RT targets. In their series, they did not detect any severe toxicity in 18 patients treated using targets created in Brain Imaging Collaboration Suite.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of sMRI in clinical practice has been hampered by data processing requirements and limited integration into the RT planning workflow. In previous studies, several time-intensive manual processing steps were required to import metabolite volumes into clinical imaging software so that they could be used in the operating room or for RT planning (17, 18). To enable integration of sMRI into clinical practice, we have developed a software platform designed specifically for the integration of sMRI into the RT planning workflow.…”
Section: Introductionmentioning
confidence: 99%